A Metalanguage for Learning: Rebalancing the Cognitive with the Socio-Material - Lim, Fei Victor; Cope, Bill; Kalantzis, Mary (Frontiers in Communication, 2022)
Technology has enabled new ways of meaning-making in the digital age, incidentally bringing with it inequities in education as a result of the differing access, resources, and experiences of students. These inequities may be rendered invisible if society and schools neither recognize, value nor set out to include in formal education the meaning-making practices from students’ lifeworlds. Such neglect can perpetuate the digital divide among students from diverse home backgrounds. The reform agenda of multiliteracies is to bring about educational justice through a pedagogy of access. In this paper, we discuss how this agenda can be operationalized in the frontline of education – the classroom. We propose a pedagogic metalanguage of transpositional grammar for the learning of multimodal literacy. “Transposition” refers to the process of moving between different forms of meaning (text, image, space, object, body, sound and speech), and changes of attention to their functions (reference, agency, structure, context and interest). In particular, we show the value of having a common shared conceptual framework with which to reflect upon and unpack multimodal meaning in terms of its forms and functions. We also describe how a repertoire of knowledge processes, rebalancing the cognitive and the socio-material, affective and embodied, can support teachers in their design for students’ multimodal literacy learning. We argue that attention to multimodal literacy in the curriculum, pedagogy, and assessment can be productively supported with a pedagogic metalanguage of transpositional grammar and discuss how this can be a step towards mediating the invisible inequities in education in the digital age.